Digitizing UK analogue magnetogram records from large geomagnetic storms of the past two centuries. Issue 1 (28th March 2022) - Beggan, Ciaran D.; Eaton, Eliot; Maume, Eleanor; Clarke, Ellen; Williamson, John; Humphries, Thomas
Abstract: Continuous geomagnetic records of the strength and direction of the Earth's field at the surface extend back to the 1840s. Over the past two centuries, eight observatories have existed in the United Kingdom, which measured the daily field variations using light‐sensitive photographic paper to produce analogue magnetograms. Around 350, 000 magnetograms have been digitally photographed at high resolution. However, converting the traces to digital values is difficult and time consuming as the magnetograms can have over‐lapping lines, low quality recordings and obscure metadata for conversion to SI units. We discuss our approach to digitizing the traces from large geomagnetic storms and highlight some of the issues to be aware of when capturing magnetic information from analogue measurements. These include cross‐checking the final digitized values with the recorded hourly mean values from observatory year books and comparing several observatory records for the same storm to catch errors such as sign inversions or incorrect 'wrap‐around' of data on the paper records. Abstract : Continuous geomagnetic records of the strength and direction of the Earth's field at the surface extend back to the 1840s of which 350, 000 magnetograms have been digitally photographed at high‐resolution. Converting the traces to digital values is difficult and time consuming as the magnetograms can have over‐lapping lines, low quality recordings and obscure metadata for conversion to SI units. We show how to digitise the traces from large geomagnetic storms and highlight issues when capturing magnetic information from analogue measurements.